COVID-19 and COVID-like Patients: A Brief Analysis and Findings of Two Deceased Cases - Balzanelli , Giosuè Mario; Distratis , Pietro; Aityan, Sergey K.; Amatulli, Felice; Catucci , Orazio; Cefalo , Angelo; Dipalma, Gianna; Inchingolo , Francesco; Lazzaro, Rita; Nguyen , Kieu C. D.; Palazzo, Davide; Hung, Van Pham; et al. (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: The predominant pattern of lung lesions in patients affected by coronavirus disease (COVID-19) disease is diffuse alveolar damage with massive thromboembolism similar as described in patients infected with severe acute respiratory syndrome coronavirus and Middle East respiratory syndrome coronaviruses. Hyaline membrane formation and pneumocyte atypical hyperplasia were frequent. Importantly, the formation of platelet–fibrin thrombi in small vessels was seen consistent with coagulopathy, which appeared to be a common feature in patients who died of COVID-19. However, many were the cases found with similar COVID-19 symptomatology though negative results from nasal-pharyngeal swab performed by reverse transcription-polymerase chain reaction (RT-PCR). This latter typology of patients, otherwise named COVID-like, showed analogous clinical signs with similar arterial blood gas, cell blood count and laboratory parameters, and same computed tomography (CT)-scan ground-glass opacities. Symptoms such as cough, fever, and difficulty breathing were highly similar as well. Both forms, COVID-19 and COVID-like, are primarily respiratory with multi-organ involvement and both revealed comparable incubation periods often with a rapid onset and unexpected decay. CASE REPORT: In this brief paper, we described two cases regarding two deceased males, one confirmed COVID-19 (RT-PCR but not CT scan) and the second a COVID-like (negative for RT-PCR but positive to CT scan with ground-glass opacity) whom condition, disease patterns, and analysis were highly similar. CONCLUSION: Improved investigation is mandatory, in which RT-PCR and CT scan procedures are completed by data from more detailed laboratory analysis, ABG analysis, BALF, and a deeper clinical assessment.